Effect of community-based physical exercise interventions carried out in primary helath care on plasma inflammatory biomarkers and cardiorespiratory fitness - Papini, Camila Bosqueiro [UNESP] (2015)
The study aims to verify the effect of community-based physical exercise interventions carried out in primary health care on plasma inflammatory biomarkers and cardiorespiratory fitness. It was performed a 1year quasi-experimental study with female participants of Physical Exercise Interventions carried out in Health Units in Rio Claro City, Sao Paulo State. Two different protocols were implemented. The Intervention 1 (two, 60 minute sessions/week) was based in the Saude Ativa Rio Claro Program (existing since 2001). The intervention 2 (three, 90 minute sessions/week) was based in the physical activity recommendation. In both interventions, aerobic, resistance muscle and stretching exercises were performed. The variables evaluated were: a) Anthropometric variables (body mass, stature, body mass index, waist and hip circumferences); b) Physical Activity level through pedometer; c) Cardiorespiratory fitness test (incremental ergoespirometric test); d) Inflammatory biomarkers (blood plasmatic dosage). The results are present in 3 articles. In the chapter 1, the results showed that the Intervention 1 was effective in reducing CRP and TNFa; and in maintaining the IL10, IL6 and insulin after 1 year of intervention. In the chapter 4, it was demonstrated that Intervention 2 decreased the LDL and glucose levels and improved the resistance insulin of participants. In chapter 5, the results indicated that participants of Intervention 2 developed a greater exercise tolerance and improved the energy cost during walking. These data suggest that cardiorespiratory fitness was enhanced. Some additional analyses indicated that participants of intervention 1 developed a greater exercise tolerance but they did not improve the energy cost during walking. Both interventions were able to improve health-related variables. The development of ...